COMPUTER TESTING SYSTEMS BASED ON THREE-LEVEL DATABASE TECHNOLOGY - Yurii S. Antonov (Інформаційні технології і засоби навчання, 2010)
Computer testing programm classification is proposed. Computer testing system based on three-level database technology is considered.